Neuroprotective Effects of Cucumeropsis mannii Seed Oil on Enzymatic Mechanisms Underlying Scopolamine-Induced Neurotoxicity in Albino Rat Brain - Ojelabi, A. O.; Onodugo, C. A.; Babalola, A. O.; Otenaike, O. E.; Brai, B. I. C.; Ajiboye, B. O.; Ajuwon, O. R.; Bamisaye, F. A. (Journal of Science, Technology and Innovation Research, 2026)
A common method for simulating cognitive decline is scopolamine-induced neurotoxicity, which disrupts neurotransmitter systems and neuronal membrane function. Therapeutic interest in natural compounds with multi-target neuroprotective potential persists. Using standard biochemical techniques to assess scopolamine-induced neurotoxicity in albino rats, this study examined the impact of CMSO on key brain homogenate neurotransmitter-related enzymes, including acetylcholinesterase (AChE), monoamine oxidase (MAO), adenosine amino esterase, and sodium–potassium ATPase (Na⁺/K⁺-ATPase). Six groups were created from a total of thirty-six adult male albino rats: Groups II through VI received scopolamine to cause neurotoxicity, while Group I acted as the normal control. Group II received no treatment, whereas the treated groups received different doses of CMSO (2.5, 5.0, and 7.5 mg/kg) or donepezil as a conventional medication. The administration of scopolamine resulted in a significant increase in adenosine amino esterase activity (p < 0.001) and a significant decrease in AChE, MAO, and Na⁺/K⁺-ATPase activities compared with the control group. This implies an aberration of the membrane-mediated ion transport, purinergic, cholinergic, and monoaminergic systems. CMSO therapy significantly enhanced AChE, MAO, and Na+/K+-ATPase activities while inhibiting adenosine amino esterase activity (p < 0.05– 0.001), thereby normalizing these parameters in a dose-dependent manner, in contrast to the scopolamine group. At the highest recommended dosage (7.5 mg/kg), enzyme activity had returned to levels corresponding to those of the control and donepezil-treated groups (p > 0.05). The study's coordinated modulation of purinergic, cholinergic, monoaminergic, and ionic homeostasis pathways demonstrates therapeutic potential comparable to that of donepezil for the treatment of cognitive impairment.